Enhancing athletes' employability after retirement from sport: the importance of competencies - Vitali, F. (8th International Congress Mountain Sport & Health. Updating Study and Research from Laboratory to Field. 7-8 November 2019, Rovereto (TN) - Italy. Programme and Book of Abstracts, 2019)
Introduction. Enhancing the employability after sport retirement is a key challenge for elite athletes (Torregrosa et al, 2015). The aim of the European project "Be a Winner in elite sports and Employment before and after athletic Retirement" (B-WISER), coordinated by the Vrije Universiteit Brussel, was to optimize the employability of elite athletes. There is a lack of empirical data and specific actions regarding the employability and employment of elite athletes during as well after athletic career. The second part (WP2) of the project was aimed at identifying the competencies required and developed by elite athletes in three final stages of their careers: active (D), former (R), and preparing for first-time employment (P). Methods. A sample of 954 elite athletes, 17-to-69-year-old (Mage=26.3, SD=10.0; 46% female) from six European countries (Belgium, Germany, Italy, Slovenia, Spain, Sweden) filled the Athletes' Competency Questionnaire for Employability (ACQE). Results. Participants reported average-to-strong possession of their competencies (M=3.77). Former elite athletes who were employed perceived the strongest possession of their competencies (M=3.90). Overall, participants reported the strongest possession for their ability to be goal-oriented, dedicated to succeeding in different life domains, and collaborative with colleagues. Participants reported the weakest possession for their ability to create a professional network, to identify themselves with the culture of their organization, and the understanding of their own career interests and options. Conclusions. The findings can be used as an evidence base for stakeholders (e.g., career counselors, employers, sport federations, educational institutions) to target specific competencies in different career stages, addressing athletes' strengths and weaknesses in preparing for and/or securing employment.